2022
DOI: 10.48550/arxiv.2210.16383
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Formalizing Anisotropic Inflation in Modified Gravity

Abstract: Motivated by the fact that the pre-inflationary era may evolve in an exotic way, in this work we formalize anisotropic evolution in the context of modified gravity, focusing on pre-inflationary and near the vicinity of the inflationary epochs. We specialize on specific metrics like Bianchi and Taub and we formalize the inflationary theory in vacuum F (R) gravity, in F (R) gravity with an extra scalar field and in Gauss-Bonnet gravity. We discuss the qualitative effects of the anisotropies on the evolution of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…see recent references in modified gravity. 13,14 It is worth mentioning that in recent article 15 an anisotropic bouncing cosmological solution in higher-derivative non-local gravity was found.…”
Section: Introductionmentioning
confidence: 99%
“…see recent references in modified gravity. 13,14 It is worth mentioning that in recent article 15 an anisotropic bouncing cosmological solution in higher-derivative non-local gravity was found.…”
Section: Introductionmentioning
confidence: 99%
“…Studying anisotropic inflation is one of current challenging projects, for example see. [13] A 1998 study by two independent research groups demonstrated that the universe is expanding at an accelerating rate [14,15]. This evidence established the existence of dark energy where the equation of state, ω, is less than −1/3 today.…”
Section: Jcap06(2024)057mentioning
confidence: 97%
“…It turns out that anisotropic inflation has been considered seriously by many people, e.g., see Ref. [15] and references therein.…”
Section: Introductionmentioning
confidence: 99%